2018
DOI: 10.1038/s41388-018-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing CD105 enhances radiation sensitivity in prostate cancer

Abstract: Radiation therapy is the primary intervention for nearly half of the patients with localized advanced prostate cancer and standard of care for recurrent disease following surgery. The development of radiation resistant disease is an obstacle for nearly 30–50% of patients undergoing radiotherapy. A better understanding of mechanisms that lead to radiation resistance could aid in the development of sensitizing agents to improve outcome. Here, we identified a radiation-resistance pathway mediated by CD105, downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…In the KEP1-11 breast cancer model, treatment with TRC105 reduced the presence of cancer-associated fibroblasts (CAFs) in primary tumors and reduced metastatic spread in an adjuvant setting [ 35 ]. In prostate cancer models, TRC105 treatment significantly potentiated the anti-tumor effects of radiation therapy, when compared to irradiation alone [ 48 ]. Additional research showed that the combination of androgen deprivation therapy (ADT) and TRC105 reduced castration-resistant prostate cancer progression through interruption of the communication between endoglin-expressing CAFs and prostate cancer cells [ 49 ].…”
Section: Preclinical Studies On Endoglin Targetingmentioning
confidence: 99%
“…In the KEP1-11 breast cancer model, treatment with TRC105 reduced the presence of cancer-associated fibroblasts (CAFs) in primary tumors and reduced metastatic spread in an adjuvant setting [ 35 ]. In prostate cancer models, TRC105 treatment significantly potentiated the anti-tumor effects of radiation therapy, when compared to irradiation alone [ 48 ]. Additional research showed that the combination of androgen deprivation therapy (ADT) and TRC105 reduced castration-resistant prostate cancer progression through interruption of the communication between endoglin-expressing CAFs and prostate cancer cells [ 49 ].…”
Section: Preclinical Studies On Endoglin Targetingmentioning
confidence: 99%
“…Studies on cancers indicated that malfunctions of BMP signaling pathways were more or less responsible for alteration in therapeutic response and make cancer cell non responsive to inhibitor or radiation [15]. Some of the reports show that inhibition of BMP pathways sensitize cancer cells to radiation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Endoglin may also represent a viable target to sensitize PC to various therapeutic modalities. Our group has previously demonstrated that radiation-resistance was mediated, in part, by CD105 downstream of the bone morphogenetic protein and transforming growth factor-β signaling whereas antagonizing CD105 with a new anti-angiogenic monoclonal antibody targeting CD105, TRC105, sensitized prostate tumors to the antitumor effects of radiation therapy in preclinical PC models in a p53-dependent manner (16). This study has several strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%